(untitled) (Encuentros, 2022)
In the family, school and other settings, violence is a common denominator in the social contexts where girls and boys converge in various regions of the country. In this context, the purpose of the article is to explore the experiences of minors within the school and to identify the teaching role in the face of the contributions they make to the processes of social, emotional and behavioral development inside and outside the classroom. This raises the importance of sharing school experiences to generate spaces for socialization and development of critical thinking through problem-solving and contributing to conflict resolution as the central axis of peacebuilding for schoolchildren. The documentary review methodology was used, categorizing the different research products and identifying them in specialized databases, managing to identify through the review, the need to redesign peacebuilding processes in the classroom according to the needs of the educational context, being the teacher a fundamental pillar of the teaching-learning process. The school must generate significant learning spaces, from a structured, challenging, and propitiatory learning of multiple stimuli and experiences for children. Also, it becomes a space to enhance the construction of knowledge and behaviors that strengthen their thinking and problem-solving.